Rodents may be major pests to crops and stored food, thus threatening food security. Among them, invasive species such as rats and mice are of particular concern since they are disseminated globally following international trade. We investigated the small - Dossou, Henri-Joel; HOUEMENOU, GUALBERT (My University, 2020)
Rodents may be major pests to crops and stored food, thus threatening food security. Among them, invasive species such as rats and mice are of particular concern since they are disseminated globally following international trade. We investigated the small mammal assemblage within the international seaport of Cotonou, Benin, in order to determine the relative importance and distribution of native vs invasive rodent species, as well as to evaluate the amount and associated costs of rodent-induced damages on imported/exported stored goods (here, rice).
Keywords: Stored products; rodent control; food security; economic losses; international trade; Rattus; Africa.